Effects of Prenatal Hypoxia on Nervous System Development and Related Diseases - Wang, Bin; Zeng, Hongtao; Liu, Jingliu; Sun, Miao (Frontiers in Neuroscience, 2021)
The fetal origins of adult disease (FOAD) hypothesis, which was proposed by David Barker in the United Kingdom in the late 1980s, posited that adult chronic diseases originated from various adverse stimuli in early fetal development. FOAD is associated with a wide range of adult chronic diseases, including cardiovascular disease, cancer, type 2 diabetes and neurological disorders such as schizophrenia, depression, anxiety, and autism. Intrauterine hypoxia/prenatal hypoxia is one of the most common complications of obstetrics and could lead to alterations in brain structure and function; therefore, it is strongly associated with neurological disorders such as cognitive impairment and anxiety. However, how fetal hypoxia results in neurological disorders remains unclear. According to the existing literature, we have summarized the causes of prenatal hypoxia, the effects of prenatal hypoxia on brain development and behavioral phenotypes, and the possible molecular mechanisms.